Field study 2 : experiencing the teaching-learning process activity sheets - Reganit, Arnulfo Aaron R.; Gavino, Renato L. (Quezon City, Philippines, 2007)
Field study is intended to provide students with practical learning experiences through observation, verification, reflection on, and actual experience of the different components of dynamic teaching- learning processes in the actual school settings.
Keywords: Field study education; learning